Comparative Performance Analysis of Different Travelling Mechanisms Based on RecurDyn. Issue 4 (March 2020) - Tang, Shufeng; Guo, Zirui; Wang, Guoqing; Wang, Xu
Abstract: According to the characteristics of different travelling mechanisms of the robot, the kinematic equations of wheeled mobile robot and tracked mobile robot are established by using the kinematic theory; the tire system and the triangle track system are established by using the multi-body dynamics simulation software RecurDyn, and the simulation analysis is carried out under the road conditions such as over the boss, according to the principle of single variable; manage the data, and we can get the difference of the robot's performance in obstacle surmounting, speed and stability. The results show that when the mobile robot adopts the travelling mechanisms of wheel shoe combination, it can improve the overall motion performance, and provide a new idea and direction for the future design of the travelling mechanism.